Analisis Perbandingan Sensitivitas Metode Simple Additive Weighting dan Weighted Product pada Pemilihan Kos di Sekitar UIN Sunan Kalijaga Yogyakarta - Irsalina Santi Khasanah; Agus Mulyanto; Muhammad Galih Wonoseto (Program Studi Sistem Informasi Fakultas Sains dan Teknologi, UIN Sunan Ampel Surabaya, 2020)
The methods in decision support systems are so diverse that we need to know which methods are more sensitive in solving a case. This study aims to compare the sensitivity of the Simple Additive Weighting method and the Weighted Product method in the selection of boarding around UIN Sunan Kalijaga Yogyakarta. Sensitivity analysis was carried out on 6 trials by changing the weight values starting from 1, 1.5, and 2 by increasing the weight values by 0.5 and 0.1. Based on research conducted, the sensitivity in the SAW Method is 31.26% and the sensitivity in the WP Method is 30.53%. In this study, the SAW method has a higher sensitivity value compared to WP.